2018
DOI: 10.1007/s12325-018-0815-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Exposure–Response Analyses of Daratumumab in Combination Therapy Regimens for Patients with Multiple Myeloma

Abstract: IntroductionDaratumumab, a human IgG monoclonal antibody targeting CD38, has demonstrated activity as monotherapy and in combination with standard-of-care regimens in multiple myeloma. Population pharmacokinetic analyses were conducted to determine the pharmacokinetics of intravenous daratumumab in combination therapy versus monotherapy, evaluate the effect of patient- and disease-related covariates on drug disposition, and examine the relationships between daratumumab exposure and efficacy/safety outcomes.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 28 publications
(41 reference statements)
7
27
0
Order By: Relevance
“…In a pharmacokinetic model, the mean half-life of daratumumab was 23.3 days, with a SD of 11.8 days. 6 This suggests that circulating daratumumab is likely present during stem cell mobilization and collection and is able to bind to In this proof of concept study, we investigated dabigatran secretion into breast milk following oral administration to non-breast-feeding women. We then estimated the systemic exposure in the neonate and investigated the potential effect on neonatal (cord blood) coagu-…”
Section: Delayed Neutrophil Engraftment In Patients Receiving Daratummentioning
confidence: 99%
“…In a pharmacokinetic model, the mean half-life of daratumumab was 23.3 days, with a SD of 11.8 days. 6 This suggests that circulating daratumumab is likely present during stem cell mobilization and collection and is able to bind to In this proof of concept study, we investigated dabigatran secretion into breast milk following oral administration to non-breast-feeding women. We then estimated the systemic exposure in the neonate and investigated the potential effect on neonatal (cord blood) coagu-…”
Section: Delayed Neutrophil Engraftment In Patients Receiving Daratummentioning
confidence: 99%
“…Previous exposure-response analysis for daratumumab monotherapy and combination therapy studies has demonstrated a strong correlation between efficacy endpoints, including overall response rate and progression-free survival as well as daratumumab serum exposure [18,19]. In contrast, no apparent relationship between serum drug exposure and adverse events was observed [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The final covariate model included body weight, albumin, type of myeloma, and sex as significant yet non-clinically relevant covariates. PK parameter estimates for individual patients treated with other regimens were obtained from previously developed population PK models [18,19,25]. Simulations were performed to predict the PK profiles for all patients who had participated in previous daratumumab studies and to compare the difference in PK between the split-and single-first dose of daratumumab among those patients.…”
Section: Population Pk Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Population PK analysis, mainly using data from the CASTOR and POLLUX trials, was performed by Xu et al47 PK was observed to be similar in single-agent and combination studies, and none of the intrinsic or extrinsic factors affected PK significantly.…”
Section: Pk and Pharmacology Of Daratumumabmentioning
confidence: 99%